Can AI Monitor Recovery Progress Remotely? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
The increasing global population, aging demographics, and the rising number of individuals with chronic conditions have highlighted the growing need for mult...
Keywords: AI in Rehabilitation Medicine; Monitor; Recovery; Progress; Artificial Intelligence; Healthcare; Digital Health